2018
DOI: 10.1080/20477724.2018.1514137
|View full text |Cite
|
Sign up to set email alerts
|

A review on inactivation methods ofToxoplasma gondiiin foods

Abstract: Toxoplasmosis is an infection caused by Toxoplasma gondii, a widespread zoonotic protozoan which poses a great threat to human health and economic well-being worldwide. It is usually acquired by ingestion of water contaminated with oocysts from the feces of infected cats or by the ingestion of raw or undercooked foodstuff containing tissue cysts. The oocyst can contaminate irrigation water and fresh edible produce. It is estimated that approximately one-third of the human population worldwide harbor this paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 116 publications
(113 reference statements)
1
28
0
Order By: Relevance
“…Our results indicated that T. gondii losses its infectivity in mice after experimental inoculation with positive meat samples after freezing for ten days at -20 ºC. This result was similar to that reported by Kotula et al (1991) and Alizadeh et al (2018) who reported that storage of meat at -20 ºC for at least three days will reduce Toxoplasma contamination in meat. Efficient veterinary inspection of meat is required for providing safe and healthy food to consumers in parallel with educational health programs about T. gondii transmission, its source of infection and control measures which should be followed especially for high risk people.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that T. gondii losses its infectivity in mice after experimental inoculation with positive meat samples after freezing for ten days at -20 ºC. This result was similar to that reported by Kotula et al (1991) and Alizadeh et al (2018) who reported that storage of meat at -20 ºC for at least three days will reduce Toxoplasma contamination in meat. Efficient veterinary inspection of meat is required for providing safe and healthy food to consumers in parallel with educational health programs about T. gondii transmission, its source of infection and control measures which should be followed especially for high risk people.…”
Section: Discussionsupporting
confidence: 92%
“…However, the relative importance of transmission via tissue cysts versus oocysts is still unclear [2]. In addition, oocysts can remain viable for long periods in the environment and can resist chemical and physical treatment currently applied in water plants, including chlorination and ozone treatment [15][16][17][18]. This paved the way for an increasingly awareness related to drinking water and the consumption of raw fruit and vegetables as putative routes for oocyst transmission.…”
Section: Introductionmentioning
confidence: 99%
“…However, as mentioned above, homeless dietary habits of high intake of processed foods and low fresh meat, fish, vegetables and fruits may have led to lower T. gondii exposure. In fact, processing food methods, including high heating, curing, cooking, freezing, or chemical methods, have been shown to denature T. gondii proteins and remove or inactivated T. gondii oocysts, constituted by 90% cysteine and tyrosine (51).…”
Section: Discussionmentioning
confidence: 99%